OUR STATE'S ATTENTION TO THE DEVELOPMENT OF INFORMATION LIBRARY CENTERS (American Journal of Pedagogical and Educational Research, 2023)
The article discusses the norms of information-library activity that should be formed on the basis of laws and norms in society, ways to increase and improve the efficiency of the service that meets the changing current needs of users of information-resource centers.